A radiotherapeutic paradox: ellagic acid sensitizes tumors while attenuating radiation-induced myocardial injury - Li, Dandan; Xie, Siqin; Yang, Sisi; Zhu, Chenghao; Lan, Haomiao; Zhu, Ke; Zhu, Ziyang; Wang, Kun; Shao, Fuqiang (Frontiers in Oncology, 2026)
BackgroundTriple-negative breast cancer (TNBC) is a highly aggressive subtype of breast cancer lacking effective targeted therapies. Radiotherapy remains a mainstay for locoregional control, but its efficacy is limited by intrinsic tumor radioresistance and the risk of radiation-induced myocardial injury (RIMI), particularly during chest irradiation. This study aimed to investigate whether ellagic acid, a naturally occurring polyphenol, could simultaneously enhance radiosensitivity in TNBC while protecting cardiac tissue from radiation-induced damage.MethodsWe employed both in vitro and in vivo TNBC models to assess the effects of ellagic acid on cell cycle progression, DNA damage response, oxidative stress, and cardiac injury. Immunofluorescence, histological staining, and echocardiography were used to evaluate tissue-level outcomes following fractionated radiotherapy, with or without EA treatment.ResultsEllagic acid effectively induced G1-phase cell cycle arrest and suppressed CDK4, thereby reducing S-phase entry and enhancing radiation-induced apoptosis in TNBC cells. In vivo, ellagic acid significantly enhanced tumor growth inhibition when combined with radiotherapy. Importantly, ellagic acid also mitigated RIMI by reducing cardiomyocyte apoptosis, preserving myocardial structure, and maintaining left ventricular systolic function. No evidence of systemic toxicity was observed.ConclusionEllagic acid exhibits a unique dual function in TNBC radiotherapy: it sensitizes tumors by targeting the CARM1-CDK4 axis while protecting the heart through potent antioxidant activity. These findings position ellagic acid as a promising adjuvant candidate to enhance therapeutic efficacy and safety in TNBC radiotherapy.